[Rezension von: García Fueyo, Beatriz, Beneficium dationis in solutum ex lege : de Roma a la Ley Española 25/2015 de 28 de Julio, de la segunda oportunidad, y RD/L 1/2020, de 5 de Mayo, de la Ley concursal] - Herrero, Luis Alberto Rivas (Revista española de derecho canónico, 2023)
Review of the book by BEATRIZ GARCÍA FUEYO which studies the dation in payment. The rule of the change of performance in the fulfillment of the obligatory bond, if there is agreement between the parties, is altered by Justinian, the year 534 AD through the legal imposition to the creditor to accept a property of the debtor who lacks cash derived from a loan, with the guarantees of the judge and evaluation of the entire estate, in addition to the definitive extinction of the credit. In force in common law and until the 19th century, with legal regulation in Spain since 2015.